Localizatation estimation usign the technique of multi-sequence positioning - Imbargk Ebra, Zuher Mesken (2015)
Wireless sensor networks (WSN) have been considered as promising tools for many location dependent applications such as area surveillance, search and rescue, mobile tracking and navigation, etc. In addition, the geographic information of sensor nodes can be critical for improving network management, topology planning, packet routing and security. Although localization plays an important role in all those systems, itself is a challenging problem due to extremely limited resources available at each low-cost sensor node. This study is focusing on using a distribution-based estimation method. The reason for selecting this method because it is considered an energy saving effort comparing to costly centralized localization scheme. The scope of the estimation in localization of sensor nodes is a Multi-Sequence Positioning (MSP) method that can be applied for a large-scale network in order to achieve accurate distance estimation in sensor deployments where the source of event has a line-of-sight to all sensors. The MATLAB is the programming will be used in the study. This is conceived as an extension of existing WSN programming frameworks. The evaluation was carried based on the error resulted from location estimation scenario compared to the current localization technique of Received Signal Strength (RSS) and the Time of Arrival (TOA). The result showed that MSP showed more efficiently in short and long range as compared to TOA. However, RSS proven to perform better than MSP in long range estimation. This was reasoned to different functional related measures in which RSS is usually perceive less obstruction and shielding of satellite signals whereas MSP can be effected by cellular networks in which it limited by the cell size.